Women, agency and the law, 1300-1700 - KANE, Bronach (Institutional Knowledge at Singapore Management University, 2013)
Based on close readings of both public and private documents - court records, churchwarden accounts, depositions, diaries, letters and pamphlets - this collection of essays presents the largely untold story of non-elite women and their dealings with the law.